(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Argentina Continental Shelf (ACS) is one of the largest and smoothest silicoclastic shelves in the world, condition that resulted from its geotectonic setting in a passive margin adjacent to a continental region with very extended and low-lying coastal plains. As a consequence, Pliocene-Quaternary glacio-eustatic sea-level fluctuations have been very important in its modelling and sedimentary characteristics. The study area is located between 35 and 39º S, the western boundary is the coastline and the eastern boundary in around 55º W that includes the outer shelf border (Fig. 1). The research is based on middle to high-resolution seismic reflection surveys and bottom/ subbottom sampling (piston cores), carried out in the context of several projects that are part of the Framework Project "Reconocimiento Geológico Geofísico del Margen Continental". The information obtained during these projects, as well as the results coming from previous projects and bibliographic compilation, allowed to gather around 4.000 km of seismic lines, 1.200 bottom samples and 92 piston cores (Fig. 2). Morphology: The ACS shows two major features (Figs. 1 and 3): inner shelf (corresponds to Terrace I, Parker et al., 1997, 1999; Violante, 2005) and outer shelf (northern part of Terrace II, Parker et al., 1997; Violante, 2005). The inner shelf extends from the coastline (or the prodelta front in the de la Plata River outlet) to the 30/40 m isobath, and includes the "Rioplatense Terrace" (RT) which represents the surface that has been modelled during the postglacial transgression but not covered by the late Holocene coastal wedge that constitutes the coastal plains. Several lower-order features modelled by the postglacial transgressive and regressive events developed on the RT surface, as the de la Plata river delta, the linear shoals systems and the La Plata Bank (Fig. 1). On the other hand, relict features composed of semiconsolidated plio-pleistocene sediments as Punta Piedras-Alto Marítimo and Restinga de los Pescadores, are significant elements in the inner shelf morphology. The outer shelf is separated from the inner shelf by a high-gradient step between 40-80 m depth (outer border of RT), which becomes, south and southeast Mar del Plata, of lower relief with a rough surface cut by transverse channels and depressions. Further east from the 80 m contourline, the outer shelf can be subdivided in two sectors: north of Querandí lighthouse it is uniformly dipping towards the shelf border, whereas in the southern part it shows a western depression (90 m depth) closer to the outer border of RT, and a eastern shoal-like elevation (75/80 m depth) near the shelf-slope transition (Fig. 3). Sedimentology: The ACS is a silicoclastic shelf where sediment characteristics and distribution are the result of dynamic, oceanographic and climatic factors. The shelf surface is covered by a relict to palimpsestic terrigenous sandy mantle which is the remnant of reworking of the deposits that constituted ancient coastal environments (barriers, coastal lagoons, estuaries) during the coastline retreat that occurred as a result of the postglacial transgressive event as well as during the sediment redistribution during the late Holocene regressive event (Urien and Ewing, 1974; Parker and Violante, 1982; Parker et al., 1999; Violante and Parker, 2000, 2004). The sandy mantle constitutes in the inner shelf a "shoal retreat massif" (in the sense of Swift, 1976) partially reworked in linear shoals systems; outcrops of the underlying plio-pleistocene substratum - partially covered by a discontinuous sheet of pebbles composed of rock fragments and caliche, beach rocks (coquinas) and sand- are common in some parts of the inner shelf. On the other hand, the outer shelf is mainly characterized by outcrops of the same substratum with minor patches of post-transgressive relict sands with a shoal-like morphology (Fig. 4). Sediment dynamic: Coastal dynamic that influenced Holocene and recent sedimentation is the result of three main sediment transport pathways: a) from the south and southeast as a consequence of the dominant oceanic circulation, that brings the relict sands stored on the shelf surface towards the coastal system, b) the regional northwards littoral transport (coastal currents) parallel to the coastline, although local inversions in the general circulation (littoral cells) are evident in the geological record, as in the Mar Chiquita Lagoon area; this transport redistributes along the coast both the shelf sands and the products of coastal erosion, c) The southwards transport of fine (muddy) sediments from the de la Plata River. Stratigraphy: The Neogene stratigraphy was defined by the application of the seismic stratigraphic method following the concepts of Mitchum et al. (1977). Six Depositional Sequences (named SD 1 to 6 from top to bottom) bounded by major seismic reflectors identified by their seismic attributes (amplitude, frequency and continuity) were recognized (Figs. 4 and 5). SD 6 (base of the sequence): corresponds to marine deposits correlated with the Miocene-Pliocene sediments known as "Paranense-Entrerriense-Chapadmalense" in the adjacent coastal areas (Parker et al., 1994, 2005). SD 5: it has seismic and sedimentological characteristics that indicate marine facies at sea changing to nearshore and fluvial facies towards the coast, and is correlated with the upper Pliocene Barranca de los Lobos Fm as well as with the Puelches Equivalente Fm defined by Yrigoyen (1975) and Parker et al. (1994). SD 4: this unit is broadly extended on the shelf with diverse seismic and litho-facies of marine, nearshore, sublittoral, low-energy coastal and continental environments, with an upwards decreasing grain-size sequence; SD 4 is equivalent to the unit known as "Interensenadense" in the adjacent coastal plains and has an upper Pliocene (2.41 Ma) age. SD 3: it is also marine/littoral and has a unique characteristic given by its discontinuous distribution in the nearshore and coastal regions as well as in some places of the shelf (Figs. 4 and 6) as a consequence of deep post-depositional erosive processes probably produced by intensification of tectonic and/ or glacioisostatic adjustments. SD 2: this unit has again a broad regional distribution, and shows different facies that represent diverse nearshore, coastal and continental environments with the particular characteristic of having been deposited as extensive barriers-coastal lagoon systems (Parker et al., 1999; Violante, 2003); it is correlated with the unit known as "Belgranense" in the adjacent coastal areas, and corresponds to the isotopic stage 5e (120 ka). SD 1: represents the uppermost sedimentary sequence formed during the last postglacial transgressive event; it is constituted by a lower transgressive system tract with different environments such as barriers/lagoons systems and estuaries, and an upper highstand system tract with regressive coastal plains, deltas and a mantle of palimpsestic and relict sands formed by reworking of the previous transgressive deposits; in most of the inner shelf surface their deposits are adjusted to the present hydrodynamic conditions (Urien and Ewing, 1974; Parker et al., 1982). Conclusive remarks: The following conclusions can be highlighted: 1) Major geomorphological features are the inner and outer shelf, which correspond to two topographically and sedimentologically different terraces separated by a step. The upper terrace (inner shelf) is a significant feature in the region which is named "Rioplatense Terrace". 2) From the sedimentological point of view, the shelf is silicoclastic; surface deposits resulted from the postglacial transgressive-regressive event. The main difference between the inner and outer shelf is given by the predominance of palimpsestic deposits in the first one and relict deposits with outcrops of the underlying Pliocene-Pleistocene substratum in the second one. 3) The Neogene stratigraphy is defined by seismicstratigraphic units representing Depositional Sequences (SD), which have been characterized on the basis of their seismic and lithological aspects and correlated with geological units known in the adjacent coastal regions. In this way it was described an uppermost, postglacial unit, followed below by a sequence of three transgressiveregressive units equivalent to the "Pampean" (Plio-Pleistocene) deposits, then a underlying unit corresponding to the "Puelches" (upper Pliocene) sands and finally the basal unit correlated with the "Paranense-Entrerriense- Chapadmalense" (Miocene-Pliocene) sequence. 4) Each SD shows a vertical sequence grading from marine (in the base) to continental (in the top) deposits in an upward decreasing grain-size distribution, therefore representing an individual and complete transgressive-regressive event. 5) The different degree of preservation of the SD in the shelf and the de la Plata River not only indicates different tectonic-glacioisostatic behaviours between both regions, but also determines the possibility that other transgressive events than those preserved in the shelf could have occurred but later completely eroded without leaving any record of their deposition.